The use of drone to study the nesting behavior of milky stork: Some preliminary observations - ANI MARDIASTUTI; YENI A. MULYANI; ANDRIE AKBAR; BASUKI WICAKSONO; TIARA RAHMAWATI; YULIA P. WULANDARI; WARSAJAYA WARSAJAYA (Society for Indonesian Biodiversity, 2023)
Abstract. Mardiastuti A, Mulyani YA, Akbar A, Wicaksono B, Rahmawati T, Wulandari YP, Warsajaya. 2023. The use of drone to study the nesting behavior of milky stork: Some preliminary observations. Biodiversitas 24: 4549-4557. The use of a drone to census waterbirds has been increasingly popular. However, study on the waterbird’s behavioral response to the drone was still limited. The objective of this study is to reveal the response of the breeding milky stork Mycteria cinerea to the drone as a new and safer tool for collecting breeding behavior data. Factors that influence the success of the observation by using a drone were also identified and a set of recommendations was formulated. The research was conducted during the breeding season of the milky stork in Pulau Rambut, a small island in Jakarta Bay, between December 2022 and March 2023. Three types of drones were tested in the pilot study, and eventually, a small manually piloted drone (Syma X25 Pro) was found to be more appropriate for behavioral study. The bird response to the drone (no, neutral, temporary, negative response) was observed through a combination of various distances and angles of the drone to the nest trees. Despite the weather obstacles, this study suggested that the milky stork mostly (17 out of 20 trials) showed no response or neutral response to the drone. Some temporary responses were detected due to some accidental events, including a sudden launch of the drone. In conclusion, a small-size, easy-to-maneuver drone that produces low noise and mild wind can be used by using a manual pilot mode to study the breeding behavior of milky storks or other similar waterbird species.